Regulating spatial charge transfer over intrinsically ultrathin-carbon-encapsulated photoanodes toward solar water splitting. Issue 6 (22nd January 2019) - Dai, Xiao-Cheng; Huang, Ming-Hui; Li, Yu-Bing; Li, Tao; Zhang, Bei-Bei; He, Yunhui; Xiao, Guangcan; Xiao, Fang-Xing
Abstract : Ultrathin carbon encapsulation, stibnite photosensitization and Co-Pi co-catalyst decoration were synergistically integrated to regulate spatial charge transfer for solar water splitting. Abstract : Photoinduced charge separation and transfer have been deemed the core factors affecting the efficiency of photoelectrocatalysis; precisely modulating the spatial migration of photo-induced charge carriers to the ideal reaction sites is of paramount importance for boosting the solar conversion efficiency of photoelectrochemical (PEC) cells. In this work, a combinatorial strategy has been developed to progressively construct highly efficient charge transport channels on the quintessential electrochemically anodized one-dimensional semiconductor framework (TiO2 nanotube arrays, TNTAs) by in situ annealing-induced intrinsic ultrathin carbon encapsulation. Antimony sulfide (Sb2 S3 ) nanocrystals were subsequently attached to the interior and exterior surfaces of the carbon-encapsulated TNTA (C–TNTA) substrate forming a well-defined ternary photoanode (C–Sb2 S3 –TNTA) capable of triggering smooth and cascade electron transfer. Cooperativity stemming from intrinsic carbon encapsulation on the surface for fast electron transport in conjunction with Sb2 S3 photosensitization for substantial visible light harvesting endows the C–Sb2 S3 –TNTA heterostructure with markedly enhanced solar-powered PEC water dissociation performances, conspicuously exceeding its single and binary counterparts. Furthermore, a hole transport pathway was further constructed by site-selective incorporation of an oxygen evolving catalyst (Co-Pi) in the ternary system via a photo-assisted electrodeposition or electrodeposition approach, which contributes to more enhanced separation efficiency and prolonged lifetime of photo-induced charge carriers together with improved photostability. It is expected that our work would afford a new frontier to intelligently mediate the spatial directional flow of photogenerated charge carriers and rationally construct efficient charge transport channels on the semiconductor-based photoelectrodes for high-efficiency solar energy harvesting and conversion.